Gambaran Pelaksanaan Tugas Kesehatan Keluarga Yang Memiliki Lansia Dengan Penyakit Hipertensi - Mukhtaruddin - -; Agrina - -; Sri - Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to description the implementation of family health function that have elderly with hypertension. The design of this research is descriptive. The research was conducted on family have elderly with hypertension in Puskesmas Sidomulyo Pekanbaru. The total sample are 70 people who were taken by using accidental sampling techniques the data was collected by quetionnaire. The analysis that was used univariate analyzis. The results showed of description familys ability to carry out the duties of health is high, 49 respondents (70%). This means that the description of the imlementation of family health function that have elderly wiht hypertension is high. The results of this study recommend for public health centre service in order to increase information to the community, especially families who have elderly people with hypertension. Keywords : Elderly, family health tasks, hypertension of elderly